Authority in therapeutic interaction: A conversation analytic study. (24th February 2021) - Smoliak, Olga; MacMartin, Clare; Hepburn, Alexa; Le Couteur, Amanda; Elliott, Robert; Quinn‐Nilas, Christopher
Abstract: A paradigmatic shift toward postmodern, collaborative practice in family therapy raises questions about how therapists can use professional authority to facilitate change and how clients can assert their knowledge and agency. We used conversation analysis to investigate how the authority to know and to determine here‐and‐now action (i.e., who does what, and how, in therapy) was negotiated and accomplished in 10 sessions of emotion‐focused therapy involving chair work. Therapists were observed to rely on a particular interactional sequence structure: stepwise entry into a directive, in which directives were preceded by a question‐answer sequence. We show how instances where clients' views were elicited prior to the delivery of a directive resulted in different interactional consequences from instances where therapists straightforwardly directed clients to perform some action. The study offers evidence concerning how therapists can facilitate chair work collaboratively and responsively.